CARDIOVASCULAR OUTCOMES AND ALL-CAUSE MORTALITY ASSOCIATED WITH APPARENT TREATMENT-RESISTANT HYPERTENSION APPLYING THE 2017 ACC/AHA GUIDELINE. (April 2021) - Jaejin, An; Sim, John; Lui, Ran; Zhou, Hui; Calhoun, David; Wei, Rong; Luong, Tiffany; Reynolds, Kristi
Abstract : Objective: The 2017 American College of Cardiology/American Heart Association (ACC/AHA) blood pressure (BP) guideline lowered BP treatment goals from < 140/90 mmHg to < 130/80 mmHg for most adults with hypertension. We investigated cardiovascular (CV) outcomes and all-cause mortality associated with apparent treatment-resistant hypertension (aTRH) according to the 2017 ACC/AHA guideline. Design and method: We included adults aged > = 18 years identified from the 2014–2015 hypertension registry in a large US integrated healthcare system. aTRH was defined as either BP above goal while taking > = 3 classes of antihypertensive medication or taking > = 4 classes regardless of BP level. We identified individuals with non-aTRH, newly classified aTRH according to 2017 ACC/AHA, controlled and uncontrolled aTRH, and refractory hypertension (RH) (BP above goal with > = 5 classes). Individuals were followed from their first date meeting the aTRH criteria (aTRH group) or first date of entering the registry (non-aTRH group) until disenrollment from the health plan, the study end date (6/30/2019), or the outcomes of interest [composite CV events (myocardial infarction, stroke, and congestive heart failure), and death]. Multivariable Cox proportional hazards models were used to compare outcomes. Results: We included 450, 181 individuals with treated hypertension [mean age 65 years, 46% White, 27% Hispanic, 14% Black, and 12% Asian], and 21% were considered as aTRH [5% newly classified aTRH, 3% controlled aTRH, 12% uncontrolled aTRH, and 1% RH]. The crude composite CV event rate was highest among patients with RH [RH = 39.9, controlled aTRH = 32.2, uncontrolled aTRH = 24.4, newly classified aTRH = 12.2, non-aTRH = 9.3 events per 1, 000 person-years]. A higher risk of CV events was associated with aTRH compared with non-aTRH [Adjusted hazard ratios (HR) (95% CI) = 1.64 (1.60, 1.69)]. Newly classified aTRH was associated with higher CV events and all-cause mortality compared with non-aTRH [HR = 1.43 (1.35, 1.52) for CV events, 1.15 (1.09, 1.20) for all-cause mortality]. Figure. No caption available. Conclusions: Newly classified aTRH, per the 2017 ACC/AHA BP guideline, was associated with a higher risk of CV events compared with non-aTRH, which supports more stringent BP goals for individuals taking 3 or more classes of antihypertensive medication.